Tubocutaneous Fistula - Krishnaveni Nayini; Clive Gie (Case Reports in Obstetrics and Gynecology)
Introduction. Tubocutaneous fistula is a very rare condition; most cases described in the literature are secondary to endometriosis, tuberculosis, and complications of child birth and gynecological operations. Case Presentation. We report a case of 40-year-old woman who presented with tubocutaneous fistula secondary to pelvic inflammatory disease which was diagnosed in the setting of persistent discharging wound in the right groin. Conclusion. Tubocutaneous fistula is a rare condition. Salpingectomy and resection of fistulous tract is the treatment of choice as is treating the underlying cause. Early diagnosis and treatment of these patients are essential for avoiding long term complications.